Segurança alimentar: um estudo com participantes dos grupos de idosos do município de Francisco Beltrão - PR - Tognon, Flávia Andriza Bedin (2015)
The food has been directly related to the quality of life of the population, so that the number of elderly people is ever increasing, it is necessary to know the food reality these individuals. Thus, this study aimed to analyze food security in participants of the groups of elderly in Francisco Beltrão - PR, to identify the incidence of elderly in a situation of food insecurity, relating socioeconomic conditions with the prevalence of food security and insecurity as well as identify and profile of the aged. Using a questionnaire with socioeconomic variables and also the Brazilian Food Insecurity Scale, were interviewed 497 elderly. The results showed that 50,9% of the elderly are food security situation, and 49.1% in food insecurity, the latter , subdividing them into mild, moderate and severe insecurity. The variables, income, gender and type of residence were observed with greatest influence on cases food insecurity. Considering that the highest rates of food insecurity are concentrated in light insecurity when there is concern about the lack of food and moderate insecurity is the lack of some types of food, you realize that some actions to financial education planning spending and familiar menu can contribute to the better use of available income.